THE IMPERATIVE RESPONSIBILITY: THE RETURN OF ETHICS IN SCIENCE (Годишен зборник на Филозофски факултет - Скопје, 2021)
At the height of self-satisfaction from the technical-technological progress, in the 20th century, it was forgotten that science and philosophy begin with wonder, astonishment. Wonder, of course, has a dimension of ignorance. Ignorance, at least according to Aristotle, is the ignorance of the reason which people are trying to find out. This is how science is born, scientific processes are started, which are similar during the solution of geometric, astronomical, or problems of modern genetics.But the rapid development of technology in the 20th century also left the man with a whole new moral situation of spreading scientific and technological achievements, a process that is an unstoppable anthropological phenomenon because it is an ontological determinant of modern man. Society, the community, really has a difficult task to balance between scientific freedom of expression and the responsibility to uphold social norms and societal values.The existing mostly heteronymous prohibitions, although necessary, are not sufficient unless the scientists themselves develop an awareness that the general humanistic moral principles and the principles of scientific critique, especially the principle of responsibility, should be followed.